2021
DOI: 10.2147/dmso.s323917
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serum Uric Acid with Clustering of Cardiovascular Risk Factors and a 10-Year Atherosclerotic Cardiovascular Disease Risk Score in Jiangsu Adults, China

Abstract: Purpose The relationship between serum uric acid (SUA) and Chinese characteristic 10-year atherosclerotic cardiovascular disease (ASCVD) risk score has not been well evaluated in Chinese populations. Aims of this cross-sectional study were to describe the correlation between SUA level and clustering of prevalent cardiovascular risk factors (CRFs) including overweight, central obesity, hypertension, diabetes and dyslipidemia, as well as the Chinese 10-year ASCVD risk score in adults from Jiangsu Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In Shanghai population, the prevalence of hyperuricemia was 17.2% (22.2% in men and 10.8% in women) in 2015 ( 18 ). In Jiangsu adults, the prevalence of hyperuricemia was 13.3% (16.9% in men and 10.3% in women) in 2015 ( 19 ). According to our real-world study, the prevalence of hyperuricemia was 32.6% (34.0% in men and 31.6% in women) among Xiamen population ( Table 1 ), which was higher than that in eastern Chinese population in 2015 and in Chinese adults in 2018–2019 ( 17 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Shanghai population, the prevalence of hyperuricemia was 17.2% (22.2% in men and 10.8% in women) in 2015 ( 18 ). In Jiangsu adults, the prevalence of hyperuricemia was 13.3% (16.9% in men and 10.3% in women) in 2015 ( 19 ). According to our real-world study, the prevalence of hyperuricemia was 32.6% (34.0% in men and 31.6% in women) among Xiamen population ( Table 1 ), which was higher than that in eastern Chinese population in 2015 and in Chinese adults in 2018–2019 ( 17 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Jiangsu adults, the prevalence of hyperuricemia was 13.3% (16.9% in men and 10.3% in women) in 2015 ( 19 ). According to our real-world study, the prevalence of hyperuricemia was 32.6% (34.0% in men and 31.6% in women) among Xiamen population ( Table 1 ), which was higher than that in eastern Chinese population in 2015 and in Chinese adults in 2018–2019 ( 17 19 ). Changes in lifestyle, eating habits and environmental factors are attributed to the development of hyperuricemia ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 Numerous epidemiological studies have suggested strong associations between serum uric acid (SUA) and CVD risk factors, [4][5][6][7] including hypertension, obesity, diabetes and dyslipidaemia. [8][9][10][11] In animalbased studies, elevated SUA levels have been found to affect cardiovascular and metabolic functions via multiple pathways, such as oxidative stress and endothelial dysfunction, and insulin resistance. 6 12-15 However, ambiguity remains regarding the associations between SUA and CVD risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, some studies have used cardiovascular risk scores to explore the relationship between hyperuricemia and CVDs risks in Chinese adults and elders. However, most of these studies are based on population samples from some specific regions or cities, and there are few representative samples covering various regions and ethnic groups in China [ 26 , 27 , 28 , 29 ]. Secondly, most of the cardiovascular risk scores used in these studies are on the basis of foreign population cohorts, while lacking studies to verify the applicability of these risk scores to Chinese populations [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%